EFEKTIVITAS STRATEGI THINK TALK WRITE (TTW) TERHADAP PENINGKATAN KEMAMPUAN BERBAHASA INGGRIS MAHASISWA UNIVERSITAS MUHAMMADIYAH BONE - Dewi Sartika Tahir; Syarifuddin Syarifuddin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The ability to use English to express ideas orally and in writing remains challenging for some students in non-English-major programs, particularly when instruction does not provide sufficient opportunities to prepare ideas, interact, and reflect on language use. This study examined changes in students’ English language proficiency following the implementation of the Think Talk Write (TTW) strategy in an English course. A total of 40 first-semester students from the Undergraduate Sports Coaching Education Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Bone, participated in this quantitative study using a quasi-experimental one-group pretest-posttest design. Over 14 meetings, learning activities involved independently preparing ideas, discussing them with peers, and organizing them into written texts. English proficiency data covering speaking, writing, vocabulary, and grammar accuracy were collected through a test and analyzed using descriptive statistics, a paired-samples t-test, N-Gain, and Cohen’s (d_z). The mean score increased from 29.39 on the pre-test to 84.49 on the post-test; the paired analysis yielded p < .001, an N-Gain of 0.78, and Cohen’s (d_z) = 10.01. Within the studied class, TTW implementation was associated with improved English proficiency and offers a learning framework that combines idea preparation, collaborative communication, and written reflection. ABSTRAK Kemampuan menggunakan bahasa Inggris untuk menyampaikan gagasan secara lisan dan tertulis masih menjadi kendala bagi sebagian mahasiswa nonprogram studi Bahasa Inggris, terutama ketika pembelajaran belum menyediakan ruang yang cukup untuk menyiapkan ide, berinteraksi, dan merefleksikan penggunaan bahasa. Penelitian ini menelaah perubahan kemampuan berbahasa Inggris mahasiswa setelah strategi Think Talk Write (TTW) diterapkan dalam pembelajaran English. Sebanyak 40 mahasiswa semester I Program Studi S1 Pendidikan Kepelatihan Olahraga, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Bone terlibat dalam penelitian kuantitatif dengan desain kuasi eksperimen one-group pretest-posttest. Selama 14 pertemuan, kegiatan pembelajaran diarahkan melalui tahap menyiapkan gagasan secara mandiri, mendiskusikannya dengan teman sebaya, dan menyusunnya dalam bentuk tulisan. Data kemampuan bahasa Inggris yang mencakup speaking, writing, vocabulary, dan grammar accuracy dikumpulkan melalui tes, kemudian dianalisis menggunakan statistik deskriptif, paired sample t-test, N-Gain, dan Cohen’s (d_z). Rerata skor berubah dari 29,39 pada pre-test menjadi 84,49 pada post-test; uji berpasangan menghasilkan p < 0,001, N-Gain 0,78, serta Cohen’s (d_z) = 10,01. Pada kelas yang diteliti, penerapan TTW berkaitan dengan peningkatan kemampuan berbahasa Inggris dan menawarkan kerangka pembelajaran yang memadukan persiapan gagasan, komunikasi kolaboratif, serta refleksi tertulis.